The quality of economic studies of cancer pharmacogenomics: a quantitative appraisal of the evidence. (October 2013) - Yang, Mo; Patel, Dhaval S; Tufail, Waqas; Issa, Amalia M
This study evaluated the quality of health economic studies of cancer pharmacogenomics (PGx). A systematic search of the literature for economic studies of PGx was conducted in four common cancers. Evaluation of study quality was carried out using the quality of health economic studies instrument. Thirty-nine articles met our eligibility criteria and were selected and accepted for further statistical analyses. The majority of articles (85%) were studies focusing on breast cancer. The overall weighted mean quality score was 85.10, with a range from 21 to 100. Eighty-seven percent of articles were categorized as good quality, whereas some 10 and 3% were categorized as moderate and poor quality, respectively. The quality of economic studies of cancer PGx is generally good but varied widely. We identified several attributes that are predictive of quality. Our findings may be useful for oncologists, health economists and decision makers interested in evaluating studies involving PGx.